2020
DOI: 10.1111/dth.13581
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the “stay‐at‐home” policy on requests for dermatology outpatient clinic visits after the COVID ‐19 outbreak

Abstract: The Coronavirus Disease 2019 (COVID-19) emerged late in Turkey but it showed a rapid progression later. We aimed to investigate the changes in the number of patients who requested a dermatology outpatient clinic visit due to the increased social and medical burden caused by COVID-19 in Turkey during the first days of the pandemic. We also examined the most common dermatologic diseases diagnosed during the COVID-19 outbreak. A statistically significant negative correlation was found between the number of COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
107
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(125 citation statements)
references
References 9 publications
14
107
1
3
Order By: Relevance
“…A large reduction in dermatologic patient volume has potential consequences as the pandemic progresses, including the accumulation of patients with worsening dermatologic conditions. Specifically, one study found an increased incidence of irritant contact dermatitis, urticaria, psoriasis, and scabies since the COVID-19 outbreak (4). In our study, dermatologists reported increased proportions of acute dermatologic issues, biopsies performed, and patients presenting for skin cancer concerns compared to pre-COVID.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…A large reduction in dermatologic patient volume has potential consequences as the pandemic progresses, including the accumulation of patients with worsening dermatologic conditions. Specifically, one study found an increased incidence of irritant contact dermatitis, urticaria, psoriasis, and scabies since the COVID-19 outbreak (4). In our study, dermatologists reported increased proportions of acute dermatologic issues, biopsies performed, and patients presenting for skin cancer concerns compared to pre-COVID.…”
Section: Discussionsupporting
confidence: 49%
“…Recent studies have shown that dermatology practices in the U.S. have limited their operations and experienced a large decrease in outpatient clinic visits, especially in areas with higher prevalence of COVID-19 (3,4). One study of 55 dermatologists in six different counties found that in March 2020, only 53% of dermatology practices were open (3).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Recently, we reported that not number but percentages of patients with scabies, psoriasis, urticaria, and scabies-related visits to dermatology outpatient clinic increased immediately 10 days after COVID-19 pandemic. 4 However, we observed a sudden rise in the number of scabies two months after the first case of COVID-19 in Turkey. This finding can be addressed in the context of the pandemicrelated "stay-at-home" policy which is very crucial to control the outbreak.…”
mentioning
confidence: 60%
“…On the other hand, although number of patients who requests for outpatient clinics that are not directly related to the pandemic cases decreased in Turkey, most of the hospitals continued to provide health care services in all branches of medicine including dermatology. 4 All these factors may be a possible explanation of why Turkey has more scabies cases than European countries.…”
mentioning
confidence: 99%
“…Pandemic hospitals were formed, and nonemergency admissions to hospitals were restricted. As a result of this situation, there had been a decrease in the number of patients who were evaluated in the dermatology outpatient clinic 7‐9 …”
Section: Introductionmentioning
confidence: 99%